A New Approach to Zakat Management for Unprecedented Times - Azim Kidwai; Mohamed El Mehdi Zidani (Center of Strategic Studies (PUSKAS) BAZNAS, 2020)
This article stresses the necessity of Zakat playing a main role in the response to humanitarian crises in the Muslim world and beyond. This will not be possible without a rethinking of the original spirit of Zakat as found in the scriptures, in addition to the adoption of innovative tools in Zakat management. As an increasing number of multi-lateral organizations are today being involved with Islamic philanthropy in general and Zakat in particular, an important topic in this discussion is about partnerships between these organizations and traditional faith-based Zakat houses and collectors. The approach suggested in this paper is a collaborative approach by which faith-based institutions would ensure the spirit of Zakat – which remains in its essence an act of faith – is preserved, while having the highest possible impact on the maximum of people in need by benefiting from the distribution networks, efficiency and other best practices of multi-lateral organizations.